2017
DOI: 10.14740/jocmr2761w
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 Deficiency and Cirrhosis Establishment

Abstract: Cirrhosis represents the final stage of chronic liver damage, which can be due to different factors such as alcohol, metabolic syndrome with liver steatosis, autoimmune diseases, drugs, toxins, and viral infection, among others. Nowadays, cirrhosis is an important health problem and it is an increasing cause of morbidity and mortality, being the 14th most common cause of death worldwide. The physiopathological pathways that lead to fibrosis and finally cirrhosis partly depend on the etiology. Nevertheless, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 133 publications
0
20
0
Order By: Relevance
“…In addition, IGF-1 reduced bone resorption through the OPG and RANKL system [ 86 ]. In end-stage liver disease, hepatocellular dysfunction and reduced GH receptors lead to low serum IGF-1 levels, subsequently causing osteoporosis [ 87 ]. Insulin, an important hormone associated with NAFLD, also affects bone remodeling by activating collagen synthesis and stimulating osteoblast proliferation and differentiation [ 88 ].…”
Section: Osteoporosis In Chronic Liver Diseasementioning
confidence: 99%
“…In addition, IGF-1 reduced bone resorption through the OPG and RANKL system [ 86 ]. In end-stage liver disease, hepatocellular dysfunction and reduced GH receptors lead to low serum IGF-1 levels, subsequently causing osteoporosis [ 87 ]. Insulin, an important hormone associated with NAFLD, also affects bone remodeling by activating collagen synthesis and stimulating osteoblast proliferation and differentiation [ 88 ].…”
Section: Osteoporosis In Chronic Liver Diseasementioning
confidence: 99%
“…In contrast, direct supplementation with IGF-1 has insulin sensitizing effects mainly mediated by the suppression of GHRH on a pituitary level and systemic reduction of GH levels, thus reducing its negative effects [ 23 ]. IGF-1 has been additionally demonstrated to have hepatoprotective effects in studies based on animal models of hepatic cirrhosis, including the decrease of oxidative stress, insulin resistance, hepatocellular apoptosis and fibrogenesis [ 26 , 28 , 29 , 30 ]. Given the metabolic differences in the effects of GH and IGF-1, it is relevant to compare the effects of supplementation with each of these hormones in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the metabolic effects of the GH–IGF-1 axis on the adipose tissue and the liver, different pathogenic mechanisms were suggested as a possible link between GHD and NAFLD [150,151], notably including insulin resistance, which is a shared common denominator of both diseases. It was repeatedly observed that mouse models with liver-specific deletion of GH receptor (GHRLD) develop insulin resistance, hepatic steatosis, dyslipidemia, and increased de novo lipogenesis [152,153].…”
Section: Gh Deficiencymentioning
confidence: 99%